A Study on Physical Parameters and Quantitative Analysis of Alcoholic and Hydro Alcoholic Extraction of Excoecaria Agallocha L in Albino Rats - Rukmini karanam; P.Kishore; K.Sumanth kumar; G.Kiran (International Journal of Allied Medical Sciences and Clinical Research, 2022)
The present study was designed to investigate the effect of different extracts of Excoecaria agallocha L. against diabetes mellitus and its related complications. Diabetes was induced by intraperitoneal administration of streptozotocin STZ (60 mg/kg) for the development of diabetic neuropathy. Treatment with different extracts of Excoecaria agallocha L significantly attenuated elevated thermal and mechanical Hyperalgesia. Elevated tactile allodynia assessed using flexible Von Frey filaments was also reversed by extracts. Treatment with both the extracts significantly attenuated the parameters of oxidative stress in sciatic nerve of diabetic neuropathic rats. These findings suggested that the Excoecaria agallocha L. may be used to manage the diabetes mellitus and its related complications such as diabetic neuropathy.